Cysticercosis in Anterior Abdominal Wall: A rare case report - Roy, Banasree C; Mondal, Gobinda (Bangladesh Journal of Medical Science, 2012)
Cysticercosis, caused by Taenia solium larva is a major public health problem especially in developing world. In this unusual form of infection man becomes the intermediate host. The encysted larval stage commonly infests brain, but muscles and subcutaneous tissues are also often affected. High resolution ultrasonography is diagnostic for subcutaneous or intramuscular cysticercosis.Here we present a rare case of anterior abdominal wall cysticercosis. DOI: http://dx.doi.org/10.3329/bjms.v11i3.11733 Bangladesh Journal of Medical Science Vol. 11 No. 03 July12